Penggunaan game online pada interaksi sosial anak di Desa Teluk Rhu Kabupaten Bengkalis - Andrila, Delita; Jelita, Jelita; Sari, Rita (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2022)
Many children at the elementary school level have played online games together. The reason why children play this online game as an amusement ride is to relieve boredom. The purpose of this study is to find out the reason why children in Teluk Rhu Village, North Rupat District, Bengkalis Regency, prefer the Free Fire online game and to find out the social interaction of children during the game. The method used is descriptive qualitative. The subjects of this study were 10 children consisting of 7 girls and 3 boys. The instruments used are interviews and observations. The results of this study state that the reason why children choose the Free Fire online game is that it is easy to access the game and the menu displayed is also not complicated. Then the social interaction of children in the category is very good, namely 69.37% while good is 30.63%.